The Effectiveness of Black's Principles with Modeling-based Learning (MbL) to Improve Students' Science Process Skills - Firza Farahdiba Daeng; Dea Ramadhana Zsa Zsa Alifah; Budi Jatmiko; Zainul Arifin Imam Supardi; Hanan Zaki Alhusni; Nina Fajriyah Citra (Universitas Negeri Surabaya, 2025)
Objective: This study aims to examine the effectiveness of the Modeling-based Learning (MbL) model in improving students’ science process skills (SPS) on the topic of Black’s Principle. SPS is essential for mastering STEM, yet remains relatively low among Indonesian students, as indicated by PISA and TIMSS results. Method: The research employed a quasi-experimental design using a pretest-posttest control group design. Two high school classes, each consisting of 30 students, participated in the study. The instruments used included an SPS test and questionnaires that measured skills such as observing, formulating hypotheses, conducting experiments, and interpreting and communicating data. Data analysis involved N-Gain calculations, normality tests, and paired t-tests to confirm statistical significance. Results: The findings revealed that the experimental class taught using the MbL model showed a significant improvement in SPS, with an average N-Gain score of 0.8 (high category). In contrast, the control class, which did not receive MbL-based instruction, only reached an average N-Gain score of 0.5 (medium category). Statistical tests confirmed the significance of these differences, demonstrating the positive impact of the MbL model on SPS development. Novelty: This study highlights the potential of the MbL approach as an innovative and effective teaching model to enhance science process skills at the secondary school level. By integrating modeling activities into learning, the MbL strategy provides students with deeper engagement and better mastery of scientific inquiry processes compared to traditional methods.